OPTIMALISASI KOMUNIKASI ORGANISASI PADA PENINGKATAN KUALITAS SUMBER DAYA MANUSIA DALAM PELATIHAN KREATIVITAS KARYAWAN PT. PELABUHAN INDONESIA (PERSERO) REGIONAL 4 MAKASSAR - Amalia , Cahaya; Hadawiah, Hadawiah; Muttaqin Mustari , Andi (UNIVERSITAS MUSLIM INDONESIA, 2022)
The purpose of this study is to find out how to Optimize Organizational Communication in Improving the Quality of Human Resources in Creativity Training of PT. Port of Indonesia (Persero) Regional 4 Makassar and how the process of implementing Organizational Communication on Improving the Quality of Human Resources in Employee Creativity Training pt. Port of Indonesia (Persero) Regional 4 Makassar. The type of research used was qualitative descriptive research with informants in this study as many as four (4) people. Data collection techniques through observation, interviews, and documentation. The results of the study, it can be concluded that employee training is one of the important activities for developing human resources. The training is only carried out 3 (Three times) a year. The forms of organizational communication that occur include communication from top to bottom, namely the delivery of messages or work instructions of PT. Port of Indonesia (Persero) Regional 4 Makassar to all employees of each division.